Social Networks, Masculinity and Emotional Intelligence in Men in the City of Quito - Freire-Muñoz, Irina (2023)
This study aims to analyze the role played by social networks, as de-territorialized spaces, in the manifestation of emotional intelligence concerning the positioning of hegemonic masculinity among men in Quito. The research design is non-experimental and cross-sectional, using a quantitative method with a descriptive-correlational scope. Two data collection instruments were used, the MASC-1 scale and the Emotional Intelligence Test. The sample consisted of 306 men from the city of Quito. The results were 41,2% each in medium and high positioning on hegemonic masculinity, and 100% of participants use social networks, mainly Facebook, Instagram and WhatsApp. On Emotional Intelligence, there is a high percentage of the Attention Factor and a low percentage in Excellence concerning the demonstration and ability to express emotions. There is a significant correlation between the use of social networks and a more remarkable ability to understand and recognize emotions in the participants.